Corporate bond market of real estate development companies in Poland - Magdalena Gostkowska-Drzewicka (e-Finanse: Financial Internet Quarterly, 2014)
The aim of the article examines the features that determine the attractivenessof bonds as a financing instrument for real estate development projects in Poland, and the share of debt securities and bonds in the financing structure of real estate development companies. The implementation of such a formulated purpose required the application of methods of statistical description. Research was conducted on the basis of data from the statistics made by Fitch Ratings Polska, Catalyst, Narodowy Bank Polski, Zwia;zek Banków Polskich and the financial statements of bond issuers. The basic research period covers the years 1998 - 2012. However, due to the lack of published data about the structure of financing of development companies, interest rates, the nominal value, the bond structure by the buyers, the type, the purpose of issuance and the form of security, long-term studies were reduced to shorter periods. Results of the research indicate that the corporate bond market of development companies was in the phase of intensive growth in 2004 - 2012. Availability of funds obtained through the issuance of bonds increased by the establishment of appropriate infrastructure in 2009. The downturn in the real estate market initiated a series of structural changes in the financing of development companies in 2008 - 2009. High margins and restrictive creditworthiness assessment brought on a search for alternative sources of financing. Due to restrictions imposed by the Act of 29th April 2012on the protection of the buyer of a dwelling or a single-family-house, it became important to provide flexible funding sources for development projects, including bond issuances.
Keywords: R31; G23; G32; 330; bond issuance; real estate development market; financing of real estate development projects